Effect of wide-narrow row arrangement in mechanical pot-seedling transplanting and plant density on yield formation and grain quality of japonica rice - Qun HU; Wei-qin JIANG; Shi QIU; Zhi-peng XING; Ya-jie HU; Bao-wei GUO; Guo-dong LIU; Hui GAO; Hong-cheng ZHANG; Hai-yan WEI (Journal of Integrative Agriculture, 2020)
Mechanical pot-seedling transplanting is an innovatively developed transplanting method that has the potential to replace mechanical carpet-seedling transplanting. However, the initial pot-seedling transplanting machine lacked optimized density spacing and limited yield potential for japonica rice. Therefore, ascertaining the optimized density by wide-narrow rows and the appropriate transplanting method for yield formation and grain quality of japonica rice is of great importance for high-quality rice production. Field experiments were conducted using two japonica rice cultivars Nanjing 9108 and Nanjing 5055 under three transplanting methods in 2016 and 2017: mechanical pot-seedling transplanting with wide-narrow row (K, average row spacing of 30 cm); equidistant row (D, 33 cmx12 cm); and mechanical carpet-seedling transplanting (T, 30 cm×12.4 cm). In addition, five different density treatments were set in K (K1–K5, from 18.62×104 to 28.49×104 hills ha–1). The results showed that the highest yield was produced by a planting density of 26.88×104 hills ha–1 in mechanical pot-seedling transplanting with wide-narrow row with a greater number of total spikelets that resulted from significantly more panicles per area and slightly more grain number per panicle, as compared with equidistant row, and yield among density in wide-narrow row showed a parabolic trend. Compared with mechanical carpet-seedling transplanting, the treatment of the highest yield increased yield significantly, which was mainly attributed to the larger sink size with improved filled-grain percentage and grain weight, higher harvest index, and increased total dry matter accumulation, especially the larger amount accumulated from heading stage to maturity stage. With the density in wide-narrow row decreasing, processing quality, appearance quality, and nutrition quality were all improved, whereas amylose content and the taste value were decreased. Compared with mechanical carpet-seedling transplanting, mechanical pot-seedling transplanting improved processing quality and nutrition quality, but decreased amylose content and deteriorated appearance quality. These results suggested that mechanical pot-seedling transplanting with wide-narrow row coupling produced a suitable planting density of 26.88×104 hills ha–1 and may be an alternative approach to improving grain yield and quality for japonica rice.